Trois notes sur le texte des fragments historiques d’Hilaire de Poitiers (Fragmenta ex opere historico, B, II, 9, 6, 2 ; 11, 2) - Guignard, Christophe (Vigiliae Christianae, 2024)
The text of Hilary of Poitiers’ Historical Fragments (Fragmenta ex opere historico, CPL 436) is affected by numerous textual corruptions. This short article discusses three problems in two difficult passages in the section on the Nicene Creed and another creed, which Hilary denounces as crypto-Arian (B, II, 9, 6, 2, p. 149, 15-21; 11, 2, p. 151, 20-152, 2).